It's who you know: a review of peer networks and academic achievement in schools - Black, Alison; Warstadt, Melissa F.; Mamas, Christoforos (Frontiers in Psychology, 2025)
Cultivating equitable academic achievement and enhancing academic functioning for youth is widely seen as one of the main missions of the public education system in the US, but educators may be overlooking critical factors for fully realizing this collective mission. This paper explores the emergent evidence on the impact of friendship and peer social networks on academic achievement and outcomes for students in K-12 public schools in the United States. In total, nine studies have been reviewed and presented. Findings suggest that peer social network selection and influence effects impact individual and group academic functioning and achievement outcomes across age groups in adolescence. Evidence across multiple studies suggests that structural effects and network position may be of special importance, particularly for low-achieving youth. However, due to publication bias issues and methodological limitations, findings should be taken cautiously. Social Network Analysis (SNA) is a quickly growing subfield of education research. There is a great need for more studies in the US, in particular those focusing on historically marginalized and underrepresented student populations (e.g., BIPOC and LGBTQ+ populations, highly mobile student groups, foster youth, students qualifying for special education support and accommodation, etc.). Another major gap identified is the need to focus on specific developmental stages, like elementary school or early adolescence, and varying environmental contexts.